A Diet Rich in Docosahexaenoic Acid Restores Liver Arachidonic Acid and Docosahexaenoic Acid Concentrations in Mice Homozygous for the Human Apolipoprotein E ε4 Allele. Issue 7 (15th June 2016) - Chouinard-Watkins, Raphaël; Pinçon, Anthony; Coulombe, Jean-Denis; Spencer, Riley; Massenavette, Laurence; Plourde, Mélanie
Abstract: Background: Metabolism of long-chain polyunsaturated fatty acids (LC-PUFAs) is disturbed in carriers of the apolipoprotein E ( APOE ) ε4 allele ( APOE4 ). More specifically, APOE4 carriers are lower responders to ω-3 (n–3) LC-PUFA supplementation; this might be because LC-PUFA transport into cells or β-oxidation is disturbed. However, high doses of dietary docosahexaenoic acid (DHA) seem to restore DHA homeostasis in APOE4 carriers, but the contribution of hepatic fatty acid (FA) transporters is unknown. Objectives: With the use of mice carrying human APOE isoforms, we sought to investigate whether a DHA-rich diet could restore DHA homeostasis in APOE4 mice and whether this involved hepatic FA transporters. Methods: Male and female mice homozygous for the APOE ε2 allele, APOE ε3 allele ( APOE3 ), and APOE4 were fed either a diet enriched with DHA (0.7 g DHA/100 g diet) or a control diet for 8 mo and were killed at 12 mo of age. Liver and plasma FA profiles were measured by GC, and FA transporter expression was evaluated by Western immunoblotting. Results: There was a significant genotype × diet interaction for hepatic concentrations of arachidonic acid (AA) and DHA ( P = 0.005 and P = 0.002, respectively) and a trend toward an interaction for liver expression of fatty acid binding protein 1 (FABP1) ( P -interaction = 0.05). APOE4 mice had 60–100% higher liver AA, DHA, and FABP1 than did APOE3 mice, but only when fed the control diet. Independent of diet, APOE4 mice had 20–30% lower plasma concentrations of AA and DHA than did APOE3 mice. Overall, mice fed the DHA diet had 50% lower concentrations of liver total FAs than did mice fed the control diet. Conclusions: These findings in transgenic mice suggest that a long-term diet rich in DHA suppresses the APOE4 -specific disturbances in hepatic transport and concentration of AA and DHA and also reduces hepatic total FA concentrations, regardless of genotype.